The Effect of Internal and External Factors on Non-Performing Financing at Islamic Commercial Banks in Indonesia - Nasir, Muhammad; AR, M. Yazid; Amri, Mustika; Handayani, Cut Fitri; Aryati, Aryati (Jurnal Samudra Ekonomi dan Bisnis, 2022)
The purpose of this study was to determine the effect of internal and external factors on non-performing financing in Islamic commercial banks and Islamic business units in Indonesia. Data is collected from publications of Bank Indonesia, the Central Statistics Agency, and the Financial Services Authority. Samples were taken from January 2010 to December 2017. Data were analyzed using Fisher’s exact test, Student's t-test, and multiple linear regression analysis. The results identify that Finance to Deposit Ratio (FDR), Capital Adequacy Ratio (CAR), inflation, and BI rate have a significant effect on non-performing financing. Based on the results, this study recommends that Islamic commercial banks and Islamic business units need to stabilize their financial ratios.